Routing on a weighted scale-free network - Hu, Mao-Bin; Jiang, R.; Wu, Yong-Hong; Wang, Wen-Xu; Wu, Q. (Elsevier, 2008)
In this paper, the packet traffic flow on weighted scale-free networks is investigated based on the local routing strategy using link weights: The capacity of links is controlled by max(βwlj,1), and the capacity of nodes is controlled by node strength: max(γsi,1). It is shown by simulations that the traffic dynamics depends strongly on the navigation parameters. These behaviors can be explained by investigating the average number of packets on nodes and delivered through links.